Use of satellite pictures for the estimates of central pressure, maximum wind speed and the storm surge heights associated with tropical storms - GUPTA , M. G.; SUD, A. M. (MAUSAM, 1975)
Using the available observations, we have derived an empirical relationship between maximum wind speed and the central pressure of the storms in the Bay of Bengal and Arabian Sea. The results obtained by this relationship are compared with the formulae available for Pacific and Atlantic storms and the satellite technique by Dvorak (1973). Utilizing the nomograms given by Das (1973), we have also given a method to predict storm surge heights from satellite pictures for the storms crossing the north Bay of Bengal.